2009
DOI: 10.1007/s10548-009-0090-9
|View full text |Cite
|
Sign up to set email alerts
|

Sound-Induced Flash Illusion is Resistant to Feedback Training

Abstract: A single flash accompanied by two auditory beeps tends to be perceived as two flashes (Shams et al. Nature 408:788, 2000, Cogn Brain Res 14:147–152, 2002). This phenomenon is known as ‘sound-induced flash illusion.’ Previous neuroimaging studies have shown that this illusion is correlated with modulation of activity in early visual cortical areas (Arden et al. Vision Res 43(23):2469–2478, 2003; Bhattacharya et al. NeuroReport 13:1727–1730, 2002; Shams et al. NeuroReport 12(17):3849–3852, 2001, Neurosci Lett 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 15 publications
(42 reference statements)
2
85
1
Order By: Relevance
“…The sound induced flash illusion is a robust multisensory phenomenon that is associated with neural activity in visual cortex (Watkins et al, 2007;Watkins et al, 2006) and is resistant to feedback training (Rosenthal et al, 2009). Illusory flash perception, however, only occurs on a proportion of trials (e.g., Shams et al, 2002) and is sensitive to manipulations of selective attention (Werkhoven et al, 2009), suggesting that top-down cognitive processes may be involved in the erroneous binding of visual and auditory signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sound induced flash illusion is a robust multisensory phenomenon that is associated with neural activity in visual cortex (Watkins et al, 2007;Watkins et al, 2006) and is resistant to feedback training (Rosenthal et al, 2009). Illusory flash perception, however, only occurs on a proportion of trials (e.g., Shams et al, 2002) and is sensitive to manipulations of selective attention (Werkhoven et al, 2009), suggesting that top-down cognitive processes may be involved in the erroneous binding of visual and auditory signals.…”
Section: Discussionmentioning
confidence: 99%
“…This flash illusion can be induced by a variety of auditory stimuli, but only occurs when the irrelevant sounds fall within a critical window of around 100 ms (Shams et al, 2000; a touch-induced flash illusion has also been reported (Violentyev et al, 2005;W ozny et al, 2008). Numerous studies have shown that the flash illusion is not explicable as a simple response bias (e.g., McCormick and Mamassian, 2008;Mishra et al, 2007;Rosenthal et al, 2009;W atkins et al, 2006), or by participants incorrectly judging the number of sounds rather than the number of flashes (e.g., Shams et al, 2002). Indeed, the illusory flash has even been shown to have measurable behavioural (Fiedler et al, 2011;McCormick and Mamassian, 2008) and neural (Mishra et al, 2008;Mishra et al, 2007;Watkins et al, 2007;Watkins et al, 2006) characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, shortterm perceptual training (<5 days) in either a combined or unisensory regimen has been shown to narrow the temporal window of multisensory binding (Powers et al 2009;Stevenson et al 2013). However, other studies have reported that the sound-induced flash illusion is largely resistance to feedback training (Rosenthal et al 2009). Equivocal findings across studies might be explained by differences in the longevity of short-term training effects and/or the inclusion feedback during learning (Powers et al 2009).…”
Section: Experience-dependent Changes In Multisensory Perceptionmentioning
confidence: 99%
“…The paddle effect is quite robust and is present in most participants (including 33 of the 35 participants in that experiment), and thus is not an effect that was driven by a subset of participants who were particularly compliant. Several other methods were used to classify the participants as more and less compliant, and each produced similar paddle effect sizes (see the appendix in Witt & Sugovic, 2013b).A final strategy has been to give explicit feedback on speed judgments (King, Tenhundfeld, & Witt, 2015, which is a strategy previously employed in crossmodal research (e.g., Rosenthal, Shimojo, & Shams, 2009). Participants classified each speed as being more like the slow or more like the fast anchor speeds.…”
mentioning
confidence: 99%